Strengthening the Socio-Cultural Competence in the Spanish as a Foreign Language Teaching - Porras González, Nohora Inés; Montero Cádiz, Manuel Medardo; González, Jan (Rastros Rostros, 2018)
Introduction: The cultural component is essential when learning a foreign language, that is why, it is necessary to promote cultural practices in the classroom that allow students not only to develop their ability to communicate with others, but also to get familiar with the cultural elements of the target language. One way to achieve this goal is through projects and meaningful practices that involve students in the foreign culture. Methodology: With the purpose of strengthening the sociocultural competence in the Spanish class, a project, that included representative cultural practices of the Hispanic culture, was implemented with primary school students in a state school in South Carolina. This project helped students to become aware of some cultural practices and involved all the member of the school community. Data was collected through observation, field notes, and questionnaires that were analyzed in order to determine categories. Conclusions: With the results it was concluded that the cultural practices carried out in the classroom facilitate the learning of the foreign language since they provide the appropriate teaching context, serve as a motivating element and give students cultural tools that are required for the effective interaction and communication with people from other cultures.